Answer: Hello there!
The system of equation given is:
y = x^2-4
y = -2x-5
And we want to solve this system:
the first step we can do is replace y in the first equation by the given in the second equation:
y = x^2-4 = -2x - 5
now we can solve it for x:
x^2-4 +2x + 5 = 0
x^2 +2x + 1 = 0
and now we can use the cuadratic equation forumla:
this is, if we have a function of the form:
ax^2 + bx + c = 0
the solutions are:
in our equation we have a=1, b = 2 and c= 1
we replace it in the formula given, and we obtain:
Now we got the value of x, and we could replace it in one of the equations and get the value of y:
y = -2x-5
y = -2*(-1) - 5 = 2 -5 = -3
then the pair is (-1, -3)
and the correct option is D.